Geländemodellierung. LandscapingSMART 3D, Maschinensteuerung, Regenwassermanagement - Petschek, Peter (Birkhäuser - an imprint of De Gruyter, 2014)
This book explains the basic principles of terrain modeling, such as contour lines, landforms, and earth mass determination, and introduces the topics of slope stabilization, rainwater management, and terrain modeling for streets and parking spaces. The second edition also includes digital technologies such as landscapingSMART, DGM, and 3D machine control. The theory is rounded out with practical examples and a problem section.